APLIKASI MULTIMEDIA INTERAKTIF UNTUK OBJEK WISATA DI KOTA PAREPARE BERBASIS WEB - Maisyaroah; Hamdan Arfandy; Hendra Surasa (KHARISMA Tech, 2018)
Kota Parepare is one of the cities in South Sulawesi that has a lot of tourism potensial. Parepare city is known as a tourist destination that is usually visited by tourist from big cities either just stopover to enjoy the beauty of the resort or just passing by. Parepare city has many tourist attraction that can be visited,but not all places in Parepare City well known by surrounding community and tourists who want to visit because of lack of W, moreover now the City of Parepare has many new attractions that must be visited. So it takes the application of a tourists object in the form of a webthat facilititate tourists to know about the existing torists attractions in the City of Parepare. This application is built in the form of web using PHP based multimedia interactive ehich unifies various elements of text, images, videos that are freely managed by the admin. This research produces is web application that provides information about tourists attractions in the city of Parepare is packaged in the form of photos, videos, maps and reviews of tourists who have visited the place.